2018
DOI: 10.3127/ajis.v22i0.1733
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Concepts and Theories in Information Systems and Technology

Abstract: A Preface to the Research Notes Special Section on Revisiting Concepts and Theories in Information Systems and Technology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…It is hoped that this conceptual framework, which to the best of knowledge of the authors is the first to conceptually and contextually integrate the two grand theories of technology acceptance to better explain how exactly a particular technology (or technologically-mediated systems, and in this case, non-profits' social media) can be designed to create and satisfy expectancies and conditions required for adoption, will help non-profits to develop effective social media strategies that widen their reach to and in non-urban communities and thus dramatically increase their ability to initiate, innovate, and deliver non-profit activities. In doing so, this paper also answers the call by Lim (2018aLim ( , 2018b in the Australasian Journal of Information Systems to revisit and reposition existing theories in information systems and technology as impetuses for greater disciplinary and managerial progress.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…It is hoped that this conceptual framework, which to the best of knowledge of the authors is the first to conceptually and contextually integrate the two grand theories of technology acceptance to better explain how exactly a particular technology (or technologically-mediated systems, and in this case, non-profits' social media) can be designed to create and satisfy expectancies and conditions required for adoption, will help non-profits to develop effective social media strategies that widen their reach to and in non-urban communities and thus dramatically increase their ability to initiate, innovate, and deliver non-profit activities. In doing so, this paper also answers the call by Lim (2018aLim ( , 2018b in the Australasian Journal of Information Systems to revisit and reposition existing theories in information systems and technology as impetuses for greater disciplinary and managerial progress.…”
Section: Introductionmentioning
confidence: 65%
“…In order for academics to contribute to the agenda of overcoming the digital divide between urban and non-urban communities and between for-profit and non-profit organizations, this paper contends that the integration and contextualization of grand theories of technology acceptance is especially important and must be considered. Specifically, the integration of grand theories will overcome the criticism of theoretical simplicity, which occurs when each theory is taken individually, whereas the contextualization of grand theories will allow for greater practical value to emerge from theorization in academic research (Lim, 2018a(Lim, , 2018b.…”
Section: Digital Dividementioning
confidence: 99%
“…Prior research (Maphalala & Adigun, 2021;Mutambara & Bayaga, 2020) has also confirmed that PU and PEOU are the most powerful predictors of technology acceptance in education. PU and PEOU are also influenced by other external factors such as social influence (SI), computer self-efficacy, and facilitating conditions (PR) (Al Kurdi et al, 2020;Chen, 2020;Lim, 2018aLim, , 2018b. According to Chen (2010), the strongest predictor of preservice teachers' acceptance of technology in the classroom is their selfefficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…a mass market for producers and a right to access for consumers). To a large degree, the sharing economy also adds to the technology aspects of marketing (Chylinski et al, 2020; Esmaeili et al, 2019; Filho et al, 2020; Gupta et al, 2019; Lim, 2018b, 2018c; Moriuchi et al, 2020; Smith, 2020; Taghizadeh et al, 2019; Taillon and Huhmann, 2019; Taylor et al, 2020; Zadeh et al, 2019; Zare et al, 2019), by providing an understanding of how technology can be used to democratise and facilitate the production and consumption of sharing practices. More important, the sharing economy extends marketing thought in the co-creation and co-innovation branch of the marketing literature (Abdul-Ghani et al, 2019; Crick, 2020; Fernandes and Remelhe, 2016; Mostafa, 2016; Whalen and Akaka, 2016), by helping marketers understand how producers and consumers can collectively innovate, create value, and engage in sustainable marketing exchanges in a profitable but inclusive way.…”
Section: What Are the Implications Of The Sharing Economy For Marketimentioning
confidence: 99%